Regulatory Burdens on Development of Automated Weeding Machines and Herbicides are Different. (1st August 2019) - Fennimore, Steven; Tourte, Laura
The pest control objective of automated weeding machines and herbicides for vegetable crops is the same, i.e., weed control, but the regulations that govern use of these tools are very different. Pesticides, including herbicides, are regulated locally, nationally and internationally and are costly for registrants to develop and conform to multiple layers of regulations.Herbicides are usually crop specific and only used in conventional crop production according to approved labels. Automated weeding machines, also known as automated weeders or intelligent cultivators, all use similar approaches to assist with weed control: cameras and computers are programmed to distinguish the crop from weeds by analyzing differences in pattern, size and color. These devices are equipped with a weed removal implement such as a cultivator knife or spray nozzle that is activated to control weeds while protecting the crop. Automated weeders are less costly to develop and lightly regulated in comparison to herbicides. Automated weeders are flexible and can be adapted for use in dozens of crops and crop configurations whether grown conventionally or organically. Despite the overwhelming need for new weed control tools in vegetable crops, substantial cost and liability barriers must be overcome in order to add a new crop to an herbicide label. Fewer regulations, and thus fewer obstacles, exist to develop and deploy automated weeders for vegetable crops. Lower development costs and less complex regulations controlling automated weeders give them a substantial advantage over the development of herbicides for vegetable crops. Vulnerability to liability claims and need for new registrations for each specialty crop or crop group makes labelling of new herbicides for vegetable crops an onerous process. Evidence for this are the 40 plus year gaps in the time since the last valuable herbicide in a vegetable crop – lettuce and pronamide are examples of this. Existing herbicides for minor crops, other than those that have lost efficacy to herbicide-resistant weeds, have been relatively reliable, inexpensive and less costly to use than hand weeding. However, herbicides face even more public scrutiny, and increased governmental regulation is likely. In addition, continuing labor shortages and rising wages restrict hand weeding as a viable economic option for weed control in vegetable crops long-term. Automated weeders have the potential to reduce the challenges associated with both herbicide and labor inputs, most notably limiting hand weeding use in vegetable crops. Strategies to contain or reduce hand weeding costs must be realized if vegetable growers in high cost areas like California are to continue to be competitive.